Demographics, clinical disease characteristics, and quality of life in a large cohort of psoriasis patients with and without psoriatic arthritis - Truong B; Rich-Garg N; Ehst BD; Deodhar AA; Ku JH; Vakil-Gilani K; Danve A; Blauvelt A (Dove Medical Press, 2015)
B Truong,1,* N Rich-Garg,2,* BD Ehst,1 AA Deodhar,2 JH Ku,2 K Vakil-Gilani,2 A Danve,2 A Blauvelt,1,3 1Department of Dermatology, Oregon Health and Science University, 2Division of Arthritis and Rheumatic Diseases, Oregon Health and Science University, 3Oregon Medical Research Center, Portland, OR, USA *These authors contributed equally to this work Innovation: What is already known about the topic: psoriasis (PsO) is a common skin disease with major impact on quality of life (QoL). Patient-reported data on QoL from large number of PsO patients with and without psoriatic arthritis (PsA) are limited. What this study adds: In a large cohort referred to a university psoriasis center, patients with PsO and concomitant PsA (~30% in this group) had greater degrees of skin and nail involvement and experienced greater negative impacts on QoL. Despite large numbers of patients with moderate-to-severe disease, use of systemic therapy by community practitioners was uncommon. Background: PsO and PsA are common diseases that have marked adverse impacts on QoL. The disease features and patient-reported QoL data comparing PsO and PsA patients are limited. Objective: To identify and compare demographics, clinical disease characteristics, and QoL scores in a large cohort of PsO patients with and without PsA. Methods: All PsO patients seen in a psoriasis specialty clinic, named the Center of Excellence for Psoriasis and Psoriatic Arthritis, were enrolled in an observational cohort. Demographic, QoL, and clinical data were collected from patient-reported questionnaires and from physical examinations performed by Center of Excellence for Psoriasis and Psoriatic Arthritis dermatologists and a rheumatologists. Cross sectional descriptive data were collected and comparisons between patients with PsO alone and those with concomitant PsA are presented. Results: A total of 568 patients were enrolled in the database. Mean age of PsO onset was 28 years and mean disease duration was 18 years. Those with family history had an earlier onset of PsO by ~7 years. Mean body surface area involvement with PsO was 14%. Mean body mass index was 30.7. Prevalence of PsA was 29.8%. PsA patients had a higher mean body surface area compared to patients with PsO alone (16.7% vs 13.4%, P<0.05), higher prevalence of psoriatic nail changes (54.4% vs 36%, P<0.0002), and worse QoL scores as assessed by the Short Form-12 (67 vs 52, P<0.00001), Psoriasis Quality of Life-12 questionnaire (62 vs 71, P<0.01), and Routine Assessment of Patient Index Data 3 (2.3 vs 4.7, P<0.01). Strikingly, 49% of patients with PsO had never received any systemic therapy. Conclusion: These data highlight that PsO has marked negative impacts on QoL, while those patients with concomitant PsA are affected to a much greater degree. Despite large numbers of patients presenting with moderate-to-severe disease, use of systemic therapy for both PsO and PsA was uncommon. Keywords: psoriasis, psoriatic arthritis, epidemiology, treatments, quality of life, patient-reported outcomes